Importance of key passes in football based on final outcome of the match and league system of competition - Barisic, V.; Dizdar, D.; Basic, D. (Acta Kinesiologica, 2016)
Based on 88 matches in 2014/2015 first Croatian football league we established the importance of key passes as a situational efficacy indicator of final outcome of the match and the league competition system. Applying Mann-Whitney test showed that key passes bring a statistically significant difference for the defeated team (p=0,02). On the other hand, observing the correlation coefficient (0,33) we can see a very low positive correlation of key passes and final placement in league system of competition. Teams which create more situations for goal scoring in a longer time period probably have a higher degree of technical and tactical quality, but a key pass indicator does not mean much if the efficiency of this type of cooperation is not high as well - meaning if the key pass does not turn into assisting. According to this, we need to keep track of key passes as situational efficacy indicators in order to eventually see the differences between winner team and defeated team and connect it to final placement.